Teaching to Learn: Ways of experiencing the practicum, teacher education and development - Mateus, Elaine; Miller, Inés; Cardoso, Janaina (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
This paper draws on ﬁndings from three interrelated research projects to analyze ways of experiencing the practicum, teacher education and development from an interventionist collaborative perspective. The shared fundamentals are 1) learning and development are societal-historical activities inherent to the nature of human beings; 2) being and identifying are functions of our total life, not only of episodic engagement with some task; 3) knowledge and knowing are integral to human active engagement with the world. Results indicate how different forms of participation provide opportunities for colearning and for developing critical reﬂexivity, ethical attitude, (pre)professional conﬁdence and autonomy.